Which of the following shows the correct process of solving -3^0 + 4.5?

A. -3^0 + 4.5 = -1 x 3^0 + 4.5 = -1 + 4.5 = -1 + 4.5 = 3.5
B. -3^0 + 4.5 = (-3)^0 + 4.5 = 1 + 4.5 = 5.5
C. -3^0 + 4.5 = -3 x 0 + 4.5 = 0 + 4.5 = 4.5
D. -3^0 + 4.5 = -3 + 4.5 = 1.5

1 answer

To solve the expression \(-3^0 + 4.5\), we need to evaluate it step by step.

  1. Calculate \(3^0\): Any non-zero number raised to the power of 0 is 1, so \(3^0 = 1\).
  2. Substitute back into the expression: Thus, \(-3^0\) is \(-1\) (since it's negative one times \(3^0\)), so we have: \[ -3^0 + 4.5 = -1 + 4.5 \]
  3. Perform the addition: Now, \(-1 + 4.5 = 3.5\).

Thus, the correct interpretation is: \[ -3^0 + 4.5 = -1 + 4.5 = 3.5 \]

Now let's examine the options:

  • A: is correct as it correctly evaluates to \(3.5\).
  • B: is incorrect because it misinterprets \(-3^0\) as \((-3)^0\).
  • C: is incorrect as it misrepresents the operation completely.
  • D: is incorrect since it does not correctly evaluate the expression.

Therefore, the correct process is represented by option A.